„Nakreślmy pewien zarys cnoty…” - helleńska arete jako fundament chrześcijańskiej doskonałości w piśmie Bazylego Wielkiego "Do młodych" - Sowa, Joanna (Vox Patrum, 2025)
In his “Adress to the Young", Basil the Great encourages the addressees to use the pagan literature they learn at school to acquire virtue, which for Christians is the path to eternal life. The analysis of the work conducted in the article aims to answer the question of how the author understands the concept of virtue (arete) and how it should be acquired. According to Basil, the essence of virtue is the dominion of reason, which is the supreme power of the soul, over the irrational drives of the body. Therefore, the concept of virtue presented in the work is ascetic (limiting the needs of the body), ethical (shaping character) and intellectual (acquiring knowledge and training the mind) in its nature. The foundations of virtue can be most easily acquired by imitating the good patterns described in the works of ancient authors, and its understanding can be deepened by familiarizing oneself with the writings of philosophers. After such preparation, the young person can more easily understand the mysteries of the "holy scriptures," which acquaint him with the principles of Christian perfection.